Enhanced oxygen diffusion in highly doped p-type Czochralski silicon - Murphy, J; Wilshaw, P; Pygall, B; Senkader, S; Falster, R (2006)
The locking of dislocations by oxygen has been investigated experimentally in Czochralski silicon (Cz-Si) with different concentrations of shallow dopants. Specimens containing well-defined arrays of dislocation half-loops were subjected to isothermal anneals in the 350-550 °C temperature range, and the stress required to bring about dislocation motion at 550 °C was then measured. This dislocation unlocking stress was found to increase with annealing time due to oxygen diffusion to the dislocation core. The dislocation unlocking stress was measured in n -type Cz-Si with a high antimony doping level (∼3.4× 1018 cm-3) and p -type Cz-Si with a low boron doping level (∼1.3× 1015 cm-3). An analysis of the data taking the different oxygen concentrations into account showed that the rate of increase in dislocation unlocking stress was unaffected by the high level of antimony doping. This indicates that a high antimony doping level has no significant effect on oxygen transport for the conditions used in this experiment. However, in p -type Cz-Si with a high boron doping level (∼5.4× 1018 cm-3), the dislocation unlocking stress was found to rise at a much faster rate than in Cz-Si with a low boron doping level or high antimony doping level. This enhancement in dislocation locking was by a factor of approximately 60 at 400 °C. By performing a numerical simulation to solve the diffusion equation for oxygen transport to a dislocation, the effective diffusivity of oxygen was deduced from the dislocation unlocking data to be 2.7× 10-6 exp (-1.4 eVkT) cm2 s-1 in the highly boron doped Cz-Si. In the temperature range studied, the effective diffusion coefficient in the highly boron doped Cz-Si was found to be approximately 44 times higher than expected in low boron doped Cz-Si with an identical oxygen concentration. © 2006 American Institute of Physics.